PELATIHAN INOVASI DAN PEMASARAN ONLINE NUGGET PISANG UPAYA PENINGKATAN EKONOMI MASYARAKAT DESA CIHERANG KECAMATAN GUNUNG SARI KABUPATEN SERANG - Listiawati Listiawati; Diah Permata Sari; Rani Sri Sumarsih (Gapenas Publisher, 2023)
The problem in CiCiherang Village is the abundance of bananas, but the lack of innovation and marketing still relies on conventional methods. One of the objectives of this activity is to improve the local economy by optimizing superior products. The method used is descriptive qualitative. This research resulted in the training